Evaluation of Some Kenyan and Nigerian Livestock Feedstuffs (Global Journal of Science Frontier Research, 2020)
This experiment was carried out to respectively evaluate the nutritive and anti-nutritive constituents of some feedstuffs and forages that are abundantly found in Kenya and Industrial rice milling wastes and Umucass 36 cassava plant meal abundantly found in Nigeria with the aim of producing them in commercial quantity for the enhancement of livestock development and feeding in Kenya and Nigeria and the entire African continent. The forages obtained in Kenya are Napier grass, Guatemala giant panicum, Boma Rhodes, Giant setaria, Mulatto and Green leaf desmodium. Rose coco, Green grams pea and Sorghum are livestock grains obtained from Kakamega County market. Rice milling waste and Umucass 36 cassava root meal (gari) were obtained from Abia State, Nigeria. They were all evaluated for their nutritive content using internationally acceptable stands. The results showed that these feedstuffs are rich in dietary nutrients and the digestibility coefficients of the forages and the feedstuffs are encouraging. Processing or non-processing of Rose coco, Green gram peas and Sorghum showed no definite pattern of response that can be traced to the processing methods used in this trial. In conclusion, the richness of these feedstuff has the potential of enhancing livestock feeding and production in these two countries if properly applied.
Keywords: forages; feeed stuffs; nutritive content and livestock